STMO-05 SURGICAL AND FUNCTIONAL OUTCOME OF AWAKE SURGERY FOR INSULAR GLIOMA - Hirono, Seiichiro (Neurooncol Adv, 2019)
BACKGROUND: Insular glioma is still challenging entity for neurosurgeons because of its deep location and the surrounding vascular structures and eloquent white matter fibers. Objective. To clarify the surgical and neurofunctional outcome of awake surgery for patients with insular glioma (IG). METHODS: We conducted a retrospective review of 42 consecutive patients with insular glioma (IG) and non-insular glioma (non-IG) who underwent awake craniotomy. In addition to surgical outcome including operative complication, the detailed objective neurocognitive evaluation were also analyzed. RESULTS: Ten IG and 32 non-IG patients were included in this study. Preoperative tumor volume in IG group was smaller than non-IG group (15.3cc, 21.9cc, p=0.14). More patients (8 in 12) in IG patients had tumor in the right hemisphere than non-IG group (12 out of 32, p=0.06). All the resection were performed according to the functional boundary decided by the cortical and subcortical mapping. Preoperatively, IG patients showed better cognitive function in the TMT-B and categorical fluency test (p=0.035, p=0.026, respectively).Postoperatively, the median residual volume and the resection rate in IG and non-IG group were 2.2cc vs 0cc (p=0.10) and 85.5% vs 100% (p=0.025) respectively, suggesting better resection in non-IG group. In terms of complications, 2 patients (20%) in IG group showed infarction in acute postoperative MR images and mild hemiparesis which recovered completely at 3-month evaluation after operation. In contrast, 16 out of 32 non-IG patients (50%) demonstrated new impaired neurocognitive function, which still persisted at final follow-up in 9 out of 16. Most of their postoperative MR images showed no ischemic lesion, suggesting white matter disconnection as main cause of new deficits. More non-IG patients demonstrated the prolonged time in TMT-A than IG patients at 3-month evaluation. CONCLUSION: Subcortical white matter disconnection, not ischemic change, are the main reason of postoperative neurocognitive dysfunction in non-IG patients.